Untangling the Overexploitation Trap: Governance, Politics of Concepts, and the Sustainability Claims of Chilean Southern Hake - Manuel E. Martínez‐González; Renato Gozzer‐Wuest; Enrique Alonso‐Población; Juan Alfaro‐Fuentes; José T. Montero; Rodrigo Wiff (Fisheries Management and Ecology, 2026)
Despite a 2013 legal reform introducing polycentric governance and an active Marine Stewardship Council (MSC) certification, persistent overexploitation of Chilean Southern hake ( Merluccius australis ) raises fundamental questions about how institutional arrangements embedding participatory management and science‐based decision‐making actually shape management outcomes. We systematically analyzed all 54 meeting minutes of Chile's Scientific Technical Committee for Demersal Resources in the Southern Austral Zone (STC‐DRSAZ) spanning its full operational period (December 2013—October 2025), covering 15 quota recommendations and 49 sessions addressing Southern hake. We reconstructed governance dynamics through a four‐category typology of decision‐making majorities and a thematic analysis of technical opinions during STC‐DRSAZ sessions. Stock status shows a slight but insufficient recovery trend (slope = 0.006/year, p ~0.02), with spawning biomass stabilized around SB t /SB 0 ~0.3—well below the MSY target of 0.4. The records reveal that management authorities exceeded STC quota recommendations in 2018 (+24%) and 2019 (+31%), and that in 20 of 36 meeting minutes, STC members expressed critical opinions on the effectiveness of the Decision Control Rules (DCRs)—distilled into seven recurring premises—ultimately leading the STC to informally abandon their application in 2024–2026. We conceptualize these dynamics as an overexploitation trap sustained by rather static DCRs that function as a political artifact rather than a science‐based management tool, entrench a short‐term management perspective, and structurally constrain the effectiveness of independent scientific advice. This trap is not a single‐stock phenomenon: the absence of legally mandated recovery programs affects six other major Patagonian demersal fisheries. Finally, we find no evidence that MSC certification has prompted meaningful improvements in stock status, lending support to growing concerns that premature market recognition may discourage rather than incentivize genuine sustainability gains.

Reproductive characteristics of the flathead mullet (Mugil cephalus Linnaeus, 1758) from the estuary of the Rapel River, Chile - Andrés Flores; Rodrigo Wiff; Leonardo Peralta; Rodolfo Farlora; Stefan Gelcich; Rodrigo Estévez (Estuarine, Coastal and Shelf Science, 2026)

Size at sex change in the protandric hermaphrodite Patagonian blenny Eleginops maclovinus ( Cuvier , 1830) in central‐southern Chile - Andrés Flores; Rodrigo Wiff; Donald I. Brown (Journal of Fish Biology, 2026)
Hermaphroditic fish species show low resilience to fishing exploitation, as alterations in sex ratio or size at sexual transition have direct implications for population fitness. The Patagonian blenny is a protandric hermaphrodite of economic importance in Chile, where basic knowledge of its life‐history traits remains scarce. Using individuals collected from the artisanal fishery, we estimated the proportion of females at length (P F ) for this species in Chile through histological analysis, and compared our findings with those of previous studies conducted in the southeast Pacific and southwest Atlantic. A total of 301 individuals were collected during March and from July to October 2022, of which 189 gonads were submitted to histological analysis. P F was estimated using a generalised linear model with a binomial error distribution. Histological analysis indicated that females possess a group‐synchronous gonadal development, whose reproductive season occurs during autumn–winter. The sexual transitional phase occurs between 30 and 40 cm in total length (L T ). The fitted ogive of P F did not differ significantly between macroscopic and histological methods ( p > 0.05). However, temporal and spatial variations in P F were evident when compared to previous studies conducted on both the Pacific and Atlantic sides. In Chile, this study revealed a decrease in the size at sexual transition for this species from 41.6 cm L T in 1974–1975 to 35.7 cm L T in 2022, highlighting the need for a monitoring system and the implementation of appropriate management measures.

Reproductive indicators highlight the need to revise the biological closure of southern hake (Merluccius australis Hutton, 1872) in Chilean Patagonia - Andrés Flores; Rodrigo Wiff; Renato Céspedes; Manuel E. Martínez González (Fisheries Research, 2025)

Genetic Population Structure of Jumbo Squid ( Dosidicus gigas ) in the Southeastern Pacific Ocean and Its Implication for Fisheries Management - M. Cecilia Pardo‐Gandarillas; Pamela Morales; Jennifer Catalán; Sergio A. Carrasco; Sebastián Hernández; Pablo A. Oyarzún; Rodrigo Wiff; Christian M. Ibáñez (Fisheries Management and Ecology, 2025)
Species with high connectivity usually lack genetic differentiation. We tested for the presence of multiple populations of jumbo squid ( Dosidicus gigas ) on the Southeastern Pacific Ocean. Samples were collected from Ecuador to southern Chile (1.5° S–38° S). Two mitochondrial genes were sequenced (COI and ND2). Jumbo squids from all sampled locations in Ecuador, Peru, and Chile, as a whole, were characterized by low genetic diversity and an absence of spatial genetic structure, which suggest the presence of a population genetic unit in the Southeastern Pacific Ocean. Absence of spatial genetic structure was associated with high vagility of adults, eggs, and paralarvae of jumbo squid. We conclude that jumbo squid should be managed as a single biological stock along the Southeastern Pacific Ocean.

Sensitivity of the stock assessment for the Antarctic krill fishery to time‐varying natural and fishing mortality - Elling Deehr Johannessen; Bjørn A. Krafft; Carl R. Donovan; Rodrigo Wiff; Bruno Caneco; Andrew Lowther (Fisheries Management and Ecology, 2024)
The stock assessment model for the Antarctic krill fishery is a population model operating on daily timesteps, which permits modeling within‐year patterns of some population dynamics. We explored the effects of including within‐year patterns in natural and fishing mortality on catch limits of krill, by incorporating temporal presence of key predator species and contemporary temporal trends of the fishing fleet. We found that inclusion of within‐year variation in natural and fishing mortalities increased catch limits. Fishing mortality had a greater effect than natural mortality despite differences in top‐down predation on krill, and potentially increased catch limits by 24% compared to the baseline model. Additionally, the stock assessment model allowed a higher catch limit when fishing was during peak summer months than autumn. Number of days with active fishing was negatively related to precautionary catch limits. Future stock assessments should incorporate contemporary spatiotemporal fishing trends and consider implementing additional ecosystem components into the model.

Modelling density on historical aggregation areas improves biomass estimates in yellow squat lobster off Chile - José Cusba; Dante Queirolo; Mauricio Ahumada; Pedro Apablaza; Jorge Paramo; Rodrigo Wiff (Fisheries Research, 2024)

Baited remote underwater video stations as a potential tool for assessing coastal rocky fishes in Chile - Alejo J. Irigoyen; Andrés Flores; Santiago Gacitúa; Pablo Merlo; Rodrigo Wiff; T. Mariella Canales (Fisheries Management and Ecology, 2024)
Coastal rocky fish species support important fishing activities, but basic information is lacking for many before catches decline. Monitoring and management of coastal rocky fish species is urgently needed in Chile, but knowledge of these species is fragmentary at best. Performance of Baited Remote Underwater Video Stations (BRUVS) for assessing rocky fish assemblages was evaluated in south‐central Chile. Seven medium‐ to large‐sized exploited species dominated fish assemblages in the survey area, including five small cryptic rocky reef fishes, one agnathan and a catshark species. These seven species represented 78% of the species targeted by commercial fishing in the survey area. Furthermore, this tool provided new information on behaviour of rocky fish species. The simple, inexpensive and light nature of single‐camera BRUVS may be crucial for maintaining monitoring programs along remote areas of Chile.

Growth estimates of young‐of‐the‐year broadnose sevengill shark, Notorynchus cepedianus , a top predator with poorly calcified vertebrae - Andrés Javier Jaureguizar; Federico Cortés; J. Matias Braccini; Rodrigo Wiff; Andrés C. Milessi (Journal of Fish Biology, 2022)
The broadnose sevengill shark, Notorynchus cepedianus (Péron, 1807), is a large marine top predator in temperate coastal ecosystems. Some aspects of its life history have been determined, but its growth pattern is yet to be fully understood. The authors used a multi‐modelling approach and a sensitivity test to estimate growth parameters from young‐of‐year (YOY) length data collected off San Antonio Cape (SAC), Argentina, a critical habitat in the Southwest Atlantic Coastal Zone (SACZ). The best selected model, a sex‐combined logistic growth model, estimated an asymptotic length ( L ∞ ) of 92.58 cm TL (95% C.I. : 86.48–105.89 cm), a growth coefficient (K) of 0.006818 days −1 (95% C.I. : 0.004948–0.008777) and a size at birth ( L 0 ) of 40.73 cm. The predicted annual growth ( i.e ., L 1 – L 0 ) was 43.2 cm TL. Males had smaller L 0 , higher K and achieved larger sizes after 1 year. The YOY in SAC attained a larger L 1 and grew faster than their Australian and South African wild counterparts. The consistent year‐round presence of YOY in the SAC highlights the importance of this area as a pupping ground and potential nursery for N. cepedianus ; this has direct implications for the allocation of research and management effort for the conservation of this species in the Southwest Atlantic.

Reproductive strategy of yellow squat lobster ( Cervimunida johni Porter, 1903): re-evaluating the maturity criteria - Andrés Flores; Rodrigo Wiff; Donald I. Brown; Mauricio Ahumada; Sebastián Larrea-Meza (Marine Biology Research, 2021)

A matter of size: the population structure of the smallest known living shark, Etmopterus perryi (Springer & Burgess, 1985), from deep waters off the Colombian Caribbean coast - Jorge Paramo; Rodrigo Wiff; Rina González (Journal of Fish Biology, 2021)
The dwarf lanternshark ( Etmopterus perryi ) is the smallest known described shark, and practically no information has been available on this species since first described in the mid‐1980s. Therefore, the aim of this work is to describe, for the first time, the population structure regarding dwarf lanternshark in the Colombian Caribbean Sea. During deep‐water research surveys conducted along the Colombian Caribbean coast, 87 stations were sampled using the swept area method. A total of 153 dwarf lanternshark individuals were caught in depths ranging from 230 to 530 m. This information was used to describe the size structures, morphological measurements including length‐at‐weight relationship, length at maturity in females and the spatial distribution of mean length and biomass of the species. The lengths of individuals ranged from 78.02 to 289.00 mm total length (TL), which is a new record of maximum length for this species. The spatial distribution of mean lengths and biomass distributions show high abundances and high relative mean lengths in the northeast area off Santa Marta and the area northwest of Riohacha. The mean biomass density in the whole prospected area was 5.52 kg km −2 . Length at 50% maturity in females was estimated in 203 mm TL (95% C.I. : 190–214 mm). Deep‐water elasmobranch species, such as the dwarf lantern shark, are expected to show extremely low resilience to fishing exploitation, even when they are not targeted by commercial fishing. Therefore, the information reported in this study can serve as a baseline upon which management measurements can be proposed for the conservation of this shark species.

Biphasic growth modelling in elasmobranchs based on asymmetric and heavy-tailed errors - Javier E. Contreras-Reyes; Rodrigo Wiff; Javier Soto; Carl R. Donovan; Miguel Araya (Environmental Biology of Fishes, 2021)

Influence of Growth and Recruitment Parameters in the Assessment and Management Variables of the Yellow Squat Lobster (Cervimunida johni) - T. Mariella Canales; Juan-Carlos Quiroz; Rodrigo Wiff; Dante Queirolo; Doris Bucarey (Journal of Marine Science and Engineering, 2020)
Fitting length data in age-structured stock assessment is a common method for evaluating hard-to-age animals, such as crustaceans. Growth specification and the uncertainty in the stock recruitment relationship are key issues in length-based assessment models. We conducted sensitivity analyses to evaluate the impact of growth and recruitment parameters on the stock assessment and management variables of the yellow squat lobster (Cervimunida johni) caught off the Chilean coast. Nine different scenarios of the length at first capture ( L a = 1 ) and the coefficient of variation at age ( c v a ) were tested for six combinations of values for the steepness parameter (h) and the recruitment variance ( σ R 2 ). We also investigated the reliability of these estimates using an operating model. Our findings indicate that the parameter related to growth, L a = 1 , has the greatest impact on the assessment and management variables of this fishery resource, with c v a having a lesser effect. Recruitment and fishing mortality estimates were the main variables affected. Parameters h and σ R 2 did not profoundly impact the variables assessed. In addition, L a = 1 was the most biased estimated parameter. We discuss that the high influence of growth parameters is related to model structure, and thus implications for determination of the status of yellow squat lobster should be addressed in the future. We recommended developing simulation protocols for the selection of growth parameters when using an age-structured model with length observations, and we believe that our findings are relevant for all Chilean fisheries with a similar stock assessment framework.

Otolith shape as a stock discrimination tool for ling ( Genypterus blacodes ) in the fjords of Chilean Patagonia - Rodrigo Wiff; Andrés Flores; Angel M. Segura; Mauricio A. Barrientos; Vilma Ojeda (New Zealand Journal of Marine and Freshwater Research, 2020)
Genypterus blacodes, in terms of its fishing history and local economic importance, is an emblematic species harvested in Chilean Patagonia (41°00’–57°00’S). Most of the current fisheries and biological knowledge of this species come from the open ocean, whereas information about the species in fjords and inner channels is fragmentary. In 2018, two research surveys targeting G. blacodes were conducted in the fjords and inner channels of Chilean Patagonia. A total of 253 pairs of sagittal otoliths were sampled at three different localities, and their contours were modelled using wavelet analysis as a tool for stock discrimination. Contours were compared using canonical analysis, and classification was performed using linear discriminant and Random Forest analyses. The results indicated that the wavelet method is efficient in modelling otolith contours, and the discriminant analyses showed differences among fishing grounds across the latitudinal gradient, thus confirming the hypothesis that G. blacodes conform to at least two separate stock units in Chilean Patagonia. Fishing grounds that were closer in space showed higher levels of misclassification. The discussion focuses on how environmental variables and the geography of fjords shape stock differences and how this information can be used for the sustainable management of G. blacodes .

The Interaction Between Stock Dynamics, Fishing and Climate Caused the Collapse of the Jack Mackerel Stock at Humboldt Current Ecosystem - Mauricio Lima; T. Mariella Canales; Rodrigo Wiff; José Montero (Frontiers in Marine Science, 2020)

Endogenous, Climate, and Fishing Influences on the Population Dynamics of Small Pelagic Fish in the Southern Humboldt Current Ecosystem - T. Mariella Canales; Mauricio Lima; Rodrigo Wiff; Javier E. Contreras-Reyes; Ursula Cifuentes; José Montero (Frontiers in Marine Science, 2020)

Reproductive biology and population structure of white warehou Seriolella caerulea and silver warehou Seriolella punctata in the austral zone off Chile - Liu Chong; Andrés Flores; Juan Carlos Quiroz; Francisco Contreras; Rodrigo Wiff (Journal of Fish Biology, 2019)
Using an extensive database compiled by scientific observers aboard commercial fishing operations between 1984 and 2014, we describe the maturity and size structures of white warehou Seriolella caerulea and silver warehou Seriolella punctata from by‐catch of the trawling industrial fisheries operating in the austral zone off Chile. Macroscopic maturity stages and gonadosomatic ( I GS ) index show mature females throughout the year and a pronounced spawning period in both austral autumn and winter seasons, with an I GS peak in July for S. punctata and August for S. caerulea . Reproductive patterns in both species show an extended spawning season (July to September) across the area between 43 and 47° S. Length–mass relationships showed significant differences between sexes in both species, where females reach a larger size. Fork length at 50% maturity was 43.5 cm for S. caerulea and 37.2 cm for S. punctata . Female catch composition is dominated by adult fish (96% for S. caerulea and 86% for S. punctata) . Currently, both species are exploited with no assessment and management‐decision framework. Therefore, information regarding reproductive biology and demographic traits becomes an important baseline to ensure adequate fisheries management for both species.

Reproductive ecology of the female pink cusk-eel (Genypterus blacodes): evaluating differences between fishery management zones in the Chilean austral zone - Laurie L Baker; Rodrigo Wiff; JC Quiroz; Andrés Flores; Renato Céspedes; Mauricio A. Barrientos; Vilma Ojeda; Claudio Gatica (Environmental Biology of Fishes, 2014)